From rural to urban land consolidation– An analysis of recent changes in Norwegian land consolidation - Helén Elisabeth Elvestad; Per Kåre Sky (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2021)
In most countries, land consolidation was first introduced in rural areas, with legislation suitable for urban areas being drafted at a later date. This is also true of Norway. The first evidence of urban competency in the legislation is found in the Land Consolidation Act from 1950. It is important to note that in Norway land consolidation remains the exclusive province of the court system. This, as far as we know, is unique for Norway. In the article we investigate how the original measures in the Land Consolidation Act for rural areas has been adapted to accommodate application in urban areas. We also investigate three urban cases brought before the Land Consolidation Court for settlement. Unfortunately, there are no national statistics that distinguish between land consolidation cases in rural and in urban areas. We can conclude that only small changes were needed to be made to the Act to suit it to land consolidation in urban areas. Properties are often difficult to use gainfully at the current time and under the current circumstances. The layout of the property is not adapted to developments that will take place. Land consolidation is therefore of great importance to urban development.
Keywords: K11; Q15; 330; Land consolidation; Land readjustment; Urban areas; Rural areas; Norway